Implementation of an ICU‐Specific Alcohol Withdrawal Syndrome Management Protocol Reduces the Need for Mechanical Ventilation. Issue 7 (27th June 2018) - Heavner, Jason J.; Akgün, Kathleen M.; Heavner, Mojdeh S.; Eng, Claire C.; Drew, Matthew; Jackson, Peter; Pritchard, David; Honiden, Shyoko
Abstract : Study Objective: Alcohol use disorders are prevalent and put patients at risk for developing alcohol withdrawal syndrome (AWS). Treatment of AWS with a symptom‐triggered protocol standardizes management and may avoid AWS‐related complications. The objective of this study was to evaluate whether implementation of a specific intensive care unit (ICU) symptom‐triggered protocol for the management of AWS was associated with improved clinical outcomes and, in particular, would reduce the risk of patients with AWS requiring mechanical ventilation. Design: Retrospective pre‐ and postprotocol implementation study. Setting: A 36‐bed closed medical ICU (MICU) at a large tertiary care teaching hospital in an urban setting. Patients: A total of 233 adults admitted to the MICU with any diagnosis of alcohol use disorders based on International Classification of Diseases, Ninth Revision codes and who received at least one dose of any benzodiazepine; of these patients, 139 were in the preprotocol era (August 2009–January 2010 and August 2010–January 2011), and 94 were in the postprotocol era (August 2012–January 2013) after implementation of the Yale Alcohol Withdrawal Protocol (YAWP) in April 2012. Measurements and Main Results: The YAWP pairs a modified Minnesota Detoxification Scale with an order set that includes benzodiazepine dosing regimens and suggests adjuvant therapies. AWS was the primary reason for ICU admission (107/233 patients [45.9%]) and did not significantly vary between study eras (p=0.2). Of the 233 patients included, 81.1% were male and 67.0% were white, which did not significantly differ by study era. Severity of illness at MICU admission did not significantly differ between patients in the preprotocol and postprotocol eras (Acute Physiology and Chronic Health Evaluation [APACHE] II median scores of 12 [interquartile range (IQR) 9–17] and 12.5 [IQR 7–16], respectively, p=0.4). Median lorazepam‐equivalent dose per MICU day, duration of benzodiazepine infusion, and use of adjuvant therapy were not significantly different between eras. MICU intubation was less common in the postprotocol era (36/139 patients [25.9%] preprotocol vs 8/94 patients [8.5%] postprotocol, p=0.0009). ICU‐related pneumonia was also decreased in the postprotocol era (30/139 patients [21.6%] preprotocol vs 10/94 patients [10.6%] postprotocol, p=0.03). After adjusting for demographics, adjuvant therapies, and APACHE II scores, protocol implementation was associated with a decreased odds of MICU intubation (odds ratio 0.13, 95% confidence interval 0.04–0.39). Conclusion: Implementation of YAWP was associated with a decreased risk of MICU intubation in patients at risk for AWS.